PERTIMBANGAN HAKIM TATA USAHA NEGARA DALAM PEMBATALAN SERTIPIKAT HAK ATAS TANAH YANG DIBEBANI HAK TANGGUNGAN (Analisis Putusan No.43/G/2019/PTUN.PDG dan Putusan No.44/G/2019/PTUN.PLG) - Almardian Asmar (UNES Journal of Swara Justisia, 2021)
Land has a dual function, namely as a social asset and a capital asset. The function of land as a social asset is a means of binding social unity among the community and the function of land as a capital asset because land has grown as a very important economic object. recorded in the land book. However, the certificate can be canceled at any time and the cancellation of the certificate of land rights will have a further impact on the process of guaranteeing the inherent Mortgage. The formulation of the problem in this research is, First, what is the consideration of the Judge of the State Administrative Court in canceling the certificate of ownership rights over land that is encumbered with mortgage rights? Second, What are the legal consequences of Certificate Cancellation based on a State Administrative Court Decision which has permanent legal force? The specification of this research is descriptive analysis. The approach used in this research is a normative juridical approach. It is called this because this research is a library research or document study which is carried out aimed only at written regulations or other legal materials. Based on the results of the research, it shows that (1) Consideration of State Administrative Court Judges in Cancellation of Certificate of Ownership of Land Burdened with Mortgage Rights (Case Analysis of Decision No. 43 / G / 2019 / PTUN.PDG) is to consider all evidence submitted by the parties to make a decision by describing the evidence relevant to the case and the judge's consideration is also based on the prevailing laws and regulations. (2) The legal consequence of the cancellation of a certificate based on the decision of the State Administrative Court which has permanent legal force is to cancel a decision, so that the result of the issuance of the cancellation decision is seen from the verdict of the court that has obtained permanent legal force (inkracht). If the Court Decision declares a certificate of ownership rights over land cancellation, then this will cause the land that has been issued a certificate of ownership rights on it to return to its original status, namely State land.